Read With Me: Key words reading scheme - Corby, Jill; Murray, William; Russell, Chris (London : 2013)
A fun reading scheme that uses the 'look and say' approach to learning to read. Essential key words are introduced and regularly repeated to assist with pronunciation and meaning. Level one is for starter readers.